Inhibitory Actions of Tropeines on the α3 Glycine Receptor Function - San Martín, Victoria P.; Burgos, Carlos F.; Marileo, Ana M.; Lara, Cesar O.; Sazo, Anggelo; Fuentealba, Jorge; Guzmán, Leonardo; Castro, Patricio A.; Aguayo, Luis G.; Moraga-Cid, Gustavo; Yévenes, Gonzalo E. (Frontiers in Pharmacology, 2019)
Glycine receptors (GlyRs) are chloride-permeable pentameric ligand-gated ion channels. The inhibitory activity of GlyRs is essential for many physiological processes, such as motor control and respiration. In addition, several pathological states, such as hyperekplexia, epilepsy and chronic pain, are associated with abnormal glycinergic inhibition. Recent studies have pointed out that positive allosteric modulators targeting the GlyR alpha3 subunit (alpha3GlyRs) displayed beneficial effects in chronic pain models. Interestingly, previous electrophysiological studies have shown that tropeines, which are a family of synthetic antagonists of the serotonin type 3 receptors (5-HT3Rs), potentiate the activity of GlyRs conformed by alpha1 subunits. However, despite its importance as a pharmacological target in chronic pain, it is currently unknown whether the alpha3GlyR function is modulated by tropeines. Using electrophysiological techniques and molecular docking simulations, here we show that tropeines are inhibitors of the alpha3GlyR function. Tropisetron, a prototypical tropeine, exerted concentration-dependent inhibitory effects on alpha3GlyRs at the low micromolar range. In addition, three other tropeines showed similar effects. Single-channel recordings show that the tropisetron inhibition is associated with a decrease in the open probability of the ion channel. Molecular docking assays suggest that tropeines preferentially bound to an agonist-free, closed state of the ion channel. The tropeine binding occurs in a discrete pocket around the vicinity of the orthosteric site within the extracellular domain of alpha3GlyR. Our results thus define the pharmacological modulation of tropeines on alpha3GlyRs. These findings may contribute to the development of GlyR-selective tropeine derivatives for basic and/or clinical applications.